Analisis Peran Kelurahan Rajeg dalam Fasilitasi Digitalisasi UMKM: Perspektif Komunikasi Pembangunan - Gading Tri Andani; Putri Ramadanti; Nanda Carolinurlita; Salma Gusni Saputri; Sekar Ayu Nur Azizah; Zaqy Azirva (Universitas Medan Area, 2026)
This study aims to analyze the role of Rajeg Village in facilitating the digitization of Micro, Small, and Medium Enterprises (MSMEs) as an effort to strengthen local economic competitiveness and independence. This study uses a descriptive qualitative approach with a case study method through in-depth interviews with the Village Head, the Head of MSMEs, and two active MSME actors. The analysis was conducted thematically by examining communication patterns, forms of facilitation, and obstacles encountered in the digitization process. The results show that the role of Rajeg Sub-District Office is still facilitative and participatory, mainly through socialization activities and cooperation with external parties such as universities. The main obstacles include low digital literacy, limited continuous training, and minimal technical support. This research expands the application of the concept of participatory development communication by showing how the role of the sub-district government as a digital facilitator can be a catalyst for socio-economic change at the community level.